Adolescent patients' perspectives on rapid-refeeding: a prospective qualitative study of an inpatient population. (1st September 2016) - Kezelman, Sarah; Rhodes, Paul; Hunt, Caroline; Anderson, Gail; Clarke, Simon; Crosby, Ross D.; Touyz, Stephen
ABSTRACT: In this study, we aimed to examine the psychological experience over the course of an inpatient treatment implementing rapid-refeeding protocol for adolescent patients with anorexia nervosa (AN). Ten female participants were included in the study and interviews were conducted on a weekly basis over the course of their admissions. Interviews were audio-recorded and analysed according to the principles of thematic analysis. Results revealed a multidimensional process broadly implicating three phases of treatment; reconciling with the 'AN' diagnosis, adjustment to treatment, and reflection and integration. Overall, these phases demonstrated a complex and often ambivalent psychological process whereby acceptance for physical and medical interventions was often in conflict with individuals' affective experiences. Clinical implications of these findings are discussed and avenues for future research highlighted.